Managing Strategic Research: An empirical analysis of science-industry collaboration in a pharmaceutical company - Jane Bjørn Vedel (Copenhagen Business School (CBS), 2014)
In recent years, the concept of `strategic research' has played a prominent role in Danish public research policy. This thesis investigates how strategic research develops in a pharmaceutical company. Politicians and policy makers have tended to see science-industry collaboration as the main strategic tool for stimulating national growth and job creation. They have also anticipated that companies and politicians in the future will have an increasingly important role in specifying societal and industrial problems that can be solved through science-industry collaborations. Hence, strategic research is today closely associated with what is termed `demand-driven innovation'. Science-industry collaboration has also attracted interest in industry, for instance, in pharmaceutical companies. However, here we find quite different ideas about strategic research and science-industry collaboration. Rather than representing a tool for providing short-term solutions, pharmaceutical companies have seen science-industry collaboration as a device for building long-term platforms of innovation. Arising from a curiosity concerning the differences between policy and corporate practices of strategic research, this thesis asks the following questions: What characterizes strategic research in a private company? Through which practices does strategic research (and science-industry collaboration) develop? What characterizes the management of strategic research?
hdl:10398/8881
Keywords: 650